2020
DOI: 10.1017/ice.2020.45
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the effectiveness of cohorting to reduce transmission of healthcare-associatedC. difficileand multidrug-resistant organisms

Abstract: Background:Cohorting of patients and staff is a control strategy often used to prevent the spread of infection in healthcare institutions. However, a comprehensive evaluation of cohorting as a prevention approach is lacking.Methods:We performed a systematic review of studies that used cohorting as part of an infection control strategy to reduce hospital-acquired infections. We included studies published between 1966 and November 30, 2019, on adult populations hospitalized in acute-care hospitals.Results:In tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 102 publications
(357 reference statements)
1
13
1
1
Order By: Relevance
“…Our staff were also reshuffled and assigned to patients in COVID-19 units to limit cross-contamination. This method of patient and staff cohorting is often used to curtail outbreaks of multi-drug resistant organisms 25 , 26 and emerging infections. 26 However, isolation and cohorting are difficult to sustain because of higher cost and increased workload for the healthcare team.…”
Section: Discussionmentioning
confidence: 99%
“…Our staff were also reshuffled and assigned to patients in COVID-19 units to limit cross-contamination. This method of patient and staff cohorting is often used to curtail outbreaks of multi-drug resistant organisms 25 , 26 and emerging infections. 26 However, isolation and cohorting are difficult to sustain because of higher cost and increased workload for the healthcare team.…”
Section: Discussionmentioning
confidence: 99%
“…According to Su et al [35], administrative control measures can be effective in reducing the transmission of infections if they are well implemented, adequately enforced and continually monitored to better facilitate staff, patients and visitors compliance. Several studies have reported that administrative control measures such as triage procedures at main entrances of the facility, limiting the number of patients and visitors to the facility, cohorting of patients and healthcare workers and physical distancing practices are all effective measures of preventing or limiting the spread of SARS-CoV-2 infection in hospitals [32,[35][36][37][38][39][40][43][44][45][46][47][49][50][51][52][53][54][55][56][57][58][59]61]. According to Lu et al [40] the establishment of infection control strategies such as material preparation and distribution, training on infection prevention measures, a triage strategy, limiting traffic into the hospital, reorganization of hospital departments to minimize the number of people present at any particular time and keeping the environment sanitized are very effective strategies to contain the spread of the SARS-CoV-2.…”
Section: Administrative Controlsmentioning
confidence: 99%
“…They concluded that there are multiple pathways of transmission and formulating healthcare teams can potentially prevent the transfer of SARS-CoV-2 to non-COVID-19 patients and staff. In a systematic review by Abad et al [46], they reported that cohorting patients and healthcare workers is an effective strategy to reduce intra-hospital transmission of infectious diseases. They observed that about 88.5% of studies have reported a significant reduction in the spread of infection when cohorting healthcare workers was implemented with other infectious disease measures such as cohorting patients and good hand hygiene practices.…”
Section: Cohorting Of Healthcare Workersmentioning
confidence: 99%
“…Evidence of intervention strategies for other types of hospital-acquired infections can also be informative. A review ( 48 ) of the effectiveness of cohorting in reducing transmission of C. difficile and multi-drug organisms found limited evidence in its effectiveness despite its widespread use.…”
Section: Discussionmentioning
confidence: 99%